Pendekatan Business Reengineering untuk Optimalisasi Proses Operasional Di PT Logistik Indonesia Cabang Palembang - Theresia Oktarina; Sinta Efriana; Olivia Angelina Batubara; Sri Andayani (Journal Of Informatics And Busisnes, 2026)
The logistics industry is required to be able to carry out operational processes efficiently, quickly, and accurately to meet the increasingly complex needs of goods distribution. PT Logistik Indonesia Palembang Branch as a cement distribution service provider faces several operational constraints, such as long fleet repair times, a high risk of work accidents, errors in cargo calculations, and administrative processes that still rely on manual activities. This study aims to analyze the operational process of cement delivery and design process improvements using a Business Process Reengineering (BPR) approach with a flowchart modeling method. The research method is carried out through observation, interviews, mapping existing processes, and identifying complaints and success factors. The results show that the implementation of BPR through streamlining process flows, digitizing operational activities, and optimizing fleet and human resource management has the potential to increase operational efficiency, reduce errors, and support improvements in the quality of distribution services.